Альдегідредуктазна активність у цитозольній фракції печінки щурів за умов різної забезпеченості раціону нутрієнтами - Лучик, Тетяна; Voloshchuk, Oksana (My University, 2021)
The activity of aldehyde reductase and the content of carbonyl derivatives in the cytosolic fraction of the liver under the conditions of diet consumption with different protein and sucrose content was studied. It was shown that in animals that consumed a high-sucrose diet, there was a significant accumulation of products of oxidative modification of proteins in the cytosolic fraction on the background of increased aldehyde reductase activity. In animals that consumed a low-protein / high-sucrose diet, there was a progressive accumulation of carbonyl derivatives against the background of reduced aldehyde reductase activity.
ALDEHYDE REDUCTASE ACTIVITY IN THE CYTOSOL FRACTION OF RATS LIVER UNDER DIFFERENT NUTRITION SUPPLIES
Keywords: нутрієнти; печінка